Tetanus-diphtheria vaccination in adults: the long-term persistence of antibodies is not dependent on polyclonal B-cell activation and the defective response to diphtheria toxoid re-vaccination is associated to HLADRB1∗01. Issue 45 (29th October 2018) - Ferlito, Claudia; Biselli, Roberto; Mariotti, Sabrina; von Hunolstein, Christina; Teloni, Raffaela; Ralli, Luisa; Pinto, Antonella; Pisani, Giulio; Tirelli, Valentina; Biondo, Michela Ileen; Salerno, Gerardo; Andreasi Bassi, Livia; et al.
Highlights: The response to Td is not influenced by co-administration of other vaccines. Tetanus and diphtheria antibody titres above 0.1 IU/ml persist for decades. Vaccine booster may be delayed beyond the current recommended10-year interval. Polyclonal B-cell stimulation is not involved in preserving Td antibody levels. HLA-DRB1∗01 allele marks subjects with a defective response to re-vaccination. Abstract: Cellular and humoral immune responses to tetanus-diphtheria vaccine (Td) were assessed in human leukocyte antigen (HLA)-typed Italian military personnel who received multiple concomitant vaccines. Td-specific antibodies and T-lymphocytes were measured in individuals with one (group-1) and more than one (group-2) Td boosters. A third group (group-3), who received several vaccines, but not Td, was studied to verify the hypothesis of the polyclonal B-cell activation as mechanism for antibody persistence. The antibody response to Td toxoids was higher in group-1, who showed lower baseline antibody levels, than in group-2 subjects. The antibody response to tetanus was higher than to diphtheria toxoid in both groups. No correlation between antibody and cellular response, and no interference in the response to Td by co-administration of different vaccines were observed. HLA-DRB1∗01 allele was detected at significant higher frequency in subjects unable to double the baseline anti-diphtheria antibody levels after the vaccination. Anti-tetanus and diphtheria antibodies half-lives were assessed and the long-lasting persistence above the threshold for protection (0.1 IU/ml) was estimated in over 65 and 20 years, respectively. No significant increase of anti-diphtheria antibodies was observed in consequence of polyclonal B-cell activation. This study emphasizes the duration of Td vaccination-induced seroprotection, suggesting that re-vaccination should probably be performed at intervals longer than 10 years. No reciprocal interference by concomitantly administered vaccines has been observed. HLA-DRB1∗01 allele was significantly associated with anti-diphtheria defective response. Finally, this study does not confirm that anti-diphtheria antibody levels are maintained by polyclonal B-cell activation. Clinical trial registry: The study was registered with NCT01807780.